Recent progress of poly(glycerol adipate)-based network materials toward tissue engineering applications - Kłusak, Anna; Gazińska, Małgorzata Anna (Frontiers in Bioengineering and Biotechnology, 2024)
The poly(glycerol adipate) (PGA) is one of the aliphatic polyesters of glycerol. The most studied biomedical application of poly(glycerol adipate) is the use of its nanoparticles as drug delivery carriers. The PGA prepolymer can be crosslinked to network materials. The biomedical application of PGA–based network materials has largely remained unexplored till recently. The PGA–based network materials, like poly(glycerol sebacate) elastomers, can be employed in tissue regeneration due to their mechanical properties. The modulus of elasticity of PGA elastomers is within the range of MPa, which corresponds to the mechanical properties of human soft tissues. This short review aims at briefly summarizing possible applications of PGA-based elastomers in tissue engineering as indicated in recent years in research publications.